Studying the Impact of the Temperature and Sorbed Water during Microwave-Induced In Situ Amorphization: A Case Study of Celecoxib and Polyvinylpyrrolidone - Nele-Johanna Hempel; Matthias M. Knopp; Korbinian Löbmann; Ragna Berthelsen (MDPI AG, 2021)
Microwave-induced in situ amorphization of a drug into a polymeric amorphous solid dispersion (ASD) has been suggested to follow a dissolution process of the drug into the polymeric network, at temperatures above the glass transition temperature (Tg) of the polymer. Thus, increasing the compact temperature, above the Tg of the polymer, is expected to increase the rate of drug dissolution in the mobile polymer, i.e., the rate of amorphization, in a direct proportional fashion. To test this hypothesis, the present study aimed at establishing a linear correlation between the compact temperature and the rate of drug amorphization using celecoxib (CCX) and the polymers polyvinylpyrrolidone (PVP) 12 and PVP17 as the model systems. Water sorbed into the drug-polymer compacts during 2 weeks of storage at 75% relative humidity was used as the dielectric heating source for the present drug amorphization process, and therefore directly affected the compact temperature during exposure to microwave radiation; the loss of water during heating was also studied. For this, compacts prepared with 30 wt% CCX, 69.5 wt% PVP12 or PVP17 and 0.5 wt% magnesium stearate (lubricant) were conditioned to have a final water content of approx. 20 wt%. The conditioned compacts were exposed to microwave radiation for 10 min at variable power outputs to achieve different compact temperatures. For compacts containing CCX in both PVP12 and PVP17, a linear correlation was established between the measured compact end temperature and the rate of drug amorphization during 10 min of exposure to microwave radiation. For compacts containing CCX in PVP12, a fully amorphous ASD was obtained after 10 min of exposure to microwave radiation with a measured compact end temperature of 71 °C. For compacts containing CCX in PVP17, it was not possible to obtain a fully amorphous ASD. The reason for this is most likely that a fast evaporation of the sorbed water increased the Tg of the conditioned drug-polymer compacts to temperatures above the highest reachable compact temperature during exposure to microwave radiation in the utilized experimental setup. Supporting this conclusion, evaporation of the sorbed water was observed to be faster for compacts containing PVP17 compared to compacts containing PVP12.